Piezoelectric Nanomaterials for Biomedical Applications - Ciofani, Gianni; Menciassi, Arianna; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Nanoscale structures and materials have been explored in many biological applications because of their novel and impressive physical and chemical properties. Such properties allow remarkable opportunities to study and interact with complex biological processes. This book analyses the state of the art of piezoelectric nanomaterials and introduces their applications in the biomedical field. Despite their impressive potentials, piezoelectric materials have not yet received significant attention for bio-applications. This book shows that the exploitation of piezoelectric nanoparticles in nanomedicine is possible and realistic, and their impressive physical properties can be useful for several applications, ranging from sensors and transducers for the detection of biomolecules to “sensible” substrates for tissue engineering or cell stimulation.
Introduction to active smart materials for biomedical applications -- Preparation of Piezoelectric Nanoparticles -- Mechanical and Electromechanical Characterization of One-Dimensional Piezoelectric Nanomaterials -- Modeling of Piezoelectric Nanodevices -- Piezoelectric Nanogenerator for Self-Powered Nanodevices -- Piezoelectric Phenomena in Biological Tissues -- Piezoelectricity and Ferroelectricity in Biomaterials: from Proteins to Self-Assembled Peptide Nanotubes -- Applications of Piezoelectricity in Nanomedicine -- Biomedical Applications of Piezoelectricity: Future Directions and Perspectives.
Keywords: Biomedical engineering; Biomaterials; Materials science; Nanotechnology; Cell culture; Biomedical Engineering and Bioengineering; Biomaterials; Characterization and Evaluation of Materials; Nanotechnology; Cell Culture